Inorganic nano-modified ground base material for artistic paint and preparation method thereof

The preparation of SEBS block copolymer chopped fibers by in-situ growth of doped Ti3SiC2 nanosheets and electrospinning processes on the SiC whisker surface has solved the problem of insufficient hardness, strength and flexibility of the ground base material, and achieved the improvement of the overall performance and the extension of the service life of the material.

CN119060573BActive Publication Date: 2025-04-29MONTAGE (FOSHAN) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411329394.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-29
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing floor base materials have insufficient performance in terms of hardness, strength and flexibility, which is difficult to take into account, and the compatibility and mechanism of the admixtures are unclear, resulting in unstable material performance.

Method used

Surface-modified doped Ti3SiC2/SiC filler is used to grow doped Ti3SiC2 nanosheets in situ on the SiC whisker surface to form a co-cluster interface. The SEBS block copolymer chopped fibers are prepared in combination with electrospinning process to enhance the mechanical properties of the material and interface bonding properties.

Benefits of technology

It significantly improves the compressive strength, hardness and flexibility of the material, solves the problem that it is difficult to take into account the strength, hardness and flexibility of traditional materials, improves the comprehensive mechanical properties and wear resistance of the material, and extends the service life of the floor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060573B_ABST
    Figure CN119060573B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of ground floor materials, and provides an inorganic nano-modified ground floor material for art paint and a preparation method thereof. The A component and the B component are made according to a mass ratio of 4:1. The A component is a surface-modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butene-styrene block copolymer short fibers, aluminate cement, 52.5-grade portland cement, quartz sand, light calcium carbonate, calcium sulfoaluminate, polycarboxylate water-reducing agent powder, acrylic resin, etc. The B component is water, silica sol, defoamer, dispersant and preservative. Preparation method: First, prepare the A and B components separately, then mix the two, and after stirring from low speed to high speed, let it stand for defoaming, scrape and roll for trimming and solidification. The surface-modified doped Ti3SiC2 / SiC filler and styrene-ethylene-butene-styrene block copolymer short fibers of present invention solve the performance problems of poor hardness, compressive strength , flexibility of the ground floor material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ground base materials, and in particular to an inorganic nano-modified ground base material for artistic paint and a preparation method thereof. Background Art

[0002] In high-end architectural decoration projects, artistic paint flooring has been increasingly widely used for its unique decorative effect and excellent comprehensive performance. As the basis of the artistic paint flooring system, the performance of the ground base material directly determines the quality and life of the entire floor. On the one hand, the ground base material must have high hardness and high compressive strength to withstand the load from the upper artistic paint and the external environment to prevent damage such as indentation and cracking; at the same time, the base material also needs to have a certain degree of flexibility to adapt to the slight deformation of the foundation and avoid problems such as bonding failure and surface layer shedding caused by the substrate being too brittle. On the other hand, the ground base material also needs to have good compatibility and adhesion with the artistic topcoat, and no delamination or peeling occurs during construction and use. Therefore, the development of a high-hardness, high-strength, and high-flexibility material is of great significance for improving the overall performance and service life of the artistic paint floor and promoting the improvement of the quality of architectural decoration projects.

[0003] At present, the base materials commonly used in artistic paint floors mainly include cement mortar and polymer mortar. Among them, the traditional cement mortar has high hardness after hardening, but low compressive strength, poor flexibility, long construction and maintenance cycle, and the bonding strength with artistic topcoat needs to be improved; while polymer mortar has good flexibility and high bonding strength, but the hardness and compressive strength are usually insufficient, and the price is relatively high. In response to the above problems, the industry mainly adopts the method of adding admixtures such as water reducers and toughening agents to modify the traditional base materials in order to take into account hardness, strength and flexibility. However, the compatibility and action mechanism of these admixtures in the cement system are still unclear, and the modification effect is often subject to the limitation of the dosage, making it difficult to fundamentally solve the problem of material performance balance. In addition, most admixture molecules lack chemical bonding with inorganic gelling materials. During construction and use, precipitation and migration are prone to occur, resulting in instability and early attenuation of material performance. Therefore, there is an urgent need to develop a new type of multifunctional ground base material, which can solve the contradiction between hardness, strength and flexibility at the source by optimizing the material composition and microstructure, so as to meet the increasingly improved performance requirements and quality pursuit of artistic paint floors. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide an inorganic nano-modified ground base material for artistic paint and a preparation method thereof, so as to solve the problem that the current ground base material has insufficient hardness, strength and flexibility.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] An inorganic nano-modified ground base material for artistic paint consists of a component A and a component B in a mass ratio of 4:1.

[0009] The component A is composed of the following raw materials in parts by mass: 5 to 12 parts of surface modified doped Ti3SiC2 / SiC filler, 2 to 6 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 5 to 10 parts of aluminate cement, 30 to 40 parts of 52.5 grade silicate cement, 15 to 25 parts of quartz sand, 5 to 10 parts of light calcium carbonate, 0.2 to 0.8 parts of calcium sulfoaluminate, 0.1 to 0.5 parts of polycarboxylate water reducer powder, 0.1 to 1 parts of acrylic resin, and 0.1 to 0.5 parts of cellulose ether suspending agent.

[0010] The component B is composed of the following raw materials in parts by mass: 50-55 parts of water, 3-5 parts of silica sol, 40-45 parts of acrylic resin, 0.1-0.3 parts of defoaming agent, 0.5-0.8 parts of dispersant, and 0.1-0.2 parts of preservative.

[0011] Furthermore, the surface-modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler includes SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers.

[0012] Furthermore, the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whisker in an in-situ growth manner.

[0013] Furthermore, the interface between the doped Ti3SiC2 nanosheets and the SiC whiskers is a coherent interface.

[0014] Furthermore, the doping element of the doped Ti3SiC2 nanosheets is iron, and the doping concentration is 1.2-3.5at%.

[0015] Furthermore, the SiC whisker has a diameter of 2 to 4 μm and a length of 20 to 45 μm.

[0016] Furthermore, the preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: in parts by weight, 3 to 6 parts of 3-aminopropylmethyldimethoxysilane and 50 to 80 parts of anhydrous ethanol are evenly mixed, and then 20 to 45 parts of doped Ti3SiC2 / SiC filler are added, and stirred at 60 to 80°C for 2 to 4 hours. After the stirring is completed, the solution is removed by filtration, and then the filtered residue is vacuum dried at room temperature for 4 to 8 hours to obtain a surface modified doped Ti3SiC2 / SiC filler.

[0017] Furthermore, the preparation method of the doped Ti3SiC2 / SiC filler is as follows: in parts by weight, 10 to 18 parts of polycarbosilane, 5 to 10 parts of Ti powder, 0.5 to 1 part of ferrocene and 60 to 100 parts of tetrahydrofuran are mixed evenly, 8 to 15 parts of SiC whiskers are added, stirred for 2 to 4 hours, and then dried completely in a vacuum drying oven at room temperature, and then placed in a vacuum tube furnace, and heat treated at a temperature of 1300 to 1500°C for 2 to 4 hours in an argon atmosphere, and then cooled to obtain the doped Ti3SiC2 / SiC filler.

[0018] Furthermore, the preparation method of the styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 20 to 45 parts of styrene-ethylene-butylene-styrene block copolymer, 3 to 8 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran are magnetically stirred and mixed for 12 to 20 hours, and then the solution is loaded into an electrospinning syringe, and then an electrospinning process is used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers are dried and chopped into styrene-ethylene-butylene-styrene block copolymer chopped fibers, wherein the process parameters of the electrospinning are: temperature of 20 to 25°C, humidity of about 35 to 45%, applied voltage of 10 to 12 kV, solution injection speed of 3 to 4 mL / h, and a working distance between the needle tip and the collector of 15 to 20 cm.

[0019] Furthermore, the preparation method of the hydroxyl-modified boron nitride nanotubes is as follows: by weight, 4 to 9 parts of boron nitride nanotubes are ultrasonically treated in a H2SO4 / HNO3 mixed acid solution with a mass ratio of 1:1 and a concentration of 10 g / L for 10 to 15 hours, and then stirred at 60 to 70°C for 8 hours, and then the ultrasonic mixture is centrifuged at a speed of 5000 to 6000 r / min for 10 to 18 minutes, and then the precipitate after centrifugation is washed with deionized water until it is neutral, and finally vacuum dried at room temperature.

[0020] Furthermore, the cellulose ether suspending agent is hydroxypropyl methylcellulose or sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0021] Furthermore, the defoaming agent is BYK-028 or BYK-034.

[0022] Furthermore, the dispersant is sodium polyacrylate or sodium polymethacrylate.

[0023] Furthermore, the preservative is 2-n-octyl-4-isothiazoline-3-one or 1,2-benzisothiazol-3-one or 2-methyl-4-isothiazoline-3-one.

[0024] The present invention adopts surface modified doped Ti3SiC2 / SiC filler for ground base material to achieve comprehensive improvement of material compressive strength, hardness and flexibility. The filler is composed of SiC whiskers and doped Ti3SiC2 nanosheets loaded on the whisker surface, and 3-aminopropylmethyldimethoxysilane is used to modify the filler surface. The technical solution of the present invention cleverly utilizes the synergistic effect of micro-nano multi-scale structure, and achieves significant improvement of material mechanical properties by rationally designing the size, morphology and interface interaction of SiC whiskers and doped Ti3SiC2 nanosheets. SiC whiskers, as micron-scale components of fillers, have excellent mechanical properties, such as high strength, high modulus and good toughness. The present invention selects SiC whiskers with a diameter of 2 to 4 μm and a length of 20 to 45 μm. This high aspect ratio fibrous structure can form an effective stress transfer network in the matrix material, thereby improving the compressive strength and hardness of the material. At the same time, the high aspect ratio of SiC whiskers also helps to enhance the flexibility of the material. Whiskers can bend and slip during the stress process, and through the dissipation of strain energy, the crack extension is delayed, and the fracture toughness of the material is improved. The surface of SiC whiskers is loaded with doped Ti3SiC2 nanosheets to form a nanoscale composite structure, which further enhances the mechanical properties of the material. Ti3SiC2 is a MAX phase ceramic that combines the characteristics of metal and ceramic, with high strength, hardness and good damage tolerance. By introducing doped Ti3SiC2 nanosheets on the surface of SiC whiskers, nanoscale stress regulation and strain coordination can be achieved. In addition, the high specific surface area and nanometer size effect of nanosheets can increase the surface energy and interface energy of the material, and improve the hardness and wear resistance of the material. Surface modification is another key link of the technical solution of the present invention. The surface treatment of doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane can significantly improve the interface bonding force between the filler and the matrix material. The organic functional groups in the silane coupling agent molecules can chemically bond or physically entangle with the matrix resin, while the inorganic siloxane groups can undergo condensation reactions with the filler surface to form stable chemical bonds. This improvement in interfacial compatibility is conducive to the effective transfer of stress between the filler and the matrix, reducing stress concentration, thereby improving the compressive strength and toughness of the material. At the same time, surface modification also helps to evenly disperse the filler in the matrix, avoid filler agglomeration, and maximize the reinforcing effect of the filler. In summary, the technical solution of the present invention achieves synergistic enhancement of mechanical properties and interface bonding between SiC whiskers and doped Ti3SiC2 nanosheets through micro-nano multi-scale structure design and surface modification. Micrometer-scale SiC whiskers provide excellent strength, hardness and toughness, and nanometer-scale doped Ti3SiC2 nanosheets further improve the crack resistance and flexibility of the material through stress regulation and strain coordination. Surface modification strengthens the interface bonding between the filler and the matrix, ensuring effective stress transfer and uniform dispersion of the filler.The synergistic effect of these factors enables the prepared inorganic nano-modified ground base material for artistic paint to achieve an optimal balance in compressive strength, hardness and flexibility, providing a new solution for the development of high-performance floor materials.

[0025] The present invention forms a uniformly distributed filler by in-situ growing doped Ti3SiC2 nanosheets on the surface of SiC whiskers, and utilizes the coherent interface between the doped Ti3SiC2 nanosheets and the SiC whiskers to achieve a reinforced bond between the filler and the matrix, thereby significantly improving the comprehensive performance of the material. In this scheme, the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whiskers in an in-situ growth manner, and this unique microstructure design has multiple advantages. First, in-situ growth can ensure that a tight chemical bond is formed between the doped Ti3SiC2 nanosheets and the SiC whiskers, thereby improving the interface bonding strength between the filler and the matrix. Secondly, the uniformly distributed nanosheets can maximize their reinforcing effect, and when subjected to external forces, they can effectively transfer stress and prevent material damage caused by stress concentration. In addition, the nanoscale doped Ti3SiC2 sheet has an ultra-high specific surface area, which can form a wider interaction with the matrix resin, further enhancing the bonding force between the filler and the matrix. More importantly, a unique coherent interface is formed between the doped Ti3SiC2 nanosheets and the SiC whiskers. A coherent interface refers to a situation in which the lattice orientation and interplanar spacing of two phases of material at the interface are completely matched, forming a continuous lattice structure. This continuous lattice structure can minimize the lattice mismatch and stress concentration at the interface, thereby greatly improving the interface bonding strength and stability. The existence of the coherent interface enables the doped Ti3SiC2 nanosheets and SiC whiskers to work together during the deformation and stress of the material, exerting a synergistic reinforcement effect, without causing the filler to fall off or the matrix to crack due to stress concentration at the interface. Through the composite design of doped Ti3SiC2 nanosheets and SiC whiskers, the filler system in this scheme exhibits excellent mechanical properties and reinforcement effects. SiC whiskers themselves have the advantages of high strength, high modulus and high hardness, while doped Ti3SiC2 nanosheets have the characteristics of high strength, high toughness and high conductivity. The composite of the two can not only make up for the shortcomings of a single filler, but also further improve the comprehensive mechanical properties of the material through synergistic effects, such as bending strength, fracture toughness and wear resistance. In summary, the technical solution of the present invention develops a high-performance inorganic nano-modified floor base material for artistic paint by in-situ growing doped Ti3SiC2 nanosheets on the surface of SiC whiskers and using the coherent interface to achieve the enhanced bonding of fillers and matrix. This material has excellent mechanical properties, wear resistance and toughness, and is expected to be widely used in the field of high-end decoration and renovation, providing a better quality and more durable material option for the construction of artistic floors.

[0026] An important design purpose of the technical solution of the present invention is to optimize the doping elements and doping concentration of doped Ti3SiC2 nanosheets to further improve the comprehensive performance of the material. After in-depth research and repeated experiments, this solution innovatively selected iron as the doping element and controlled the doping concentration within the range of 1.2 to 3.5 at%. This unique doping design is not only conducive to the uniform dispersion of Ti3SiC2 nanosheets on the surface of SiC whiskers, but also can enhance the mechanical properties of the material through multiple mechanisms, especially improve the bending strength, fracture toughness and wear resistance of the material. First, the doping of iron elements can significantly affect the surface properties of Ti3SiC2 nanosheets, thereby promoting their uniform dispersion on SiC whiskers. The appropriate amount of iron atom doping can adjust the surface energy and surface charge distribution of Ti3SiC2 nanosheets and enhance the interfacial interaction between them and SiC whiskers. This enhanced interfacial effect can effectively inhibit the agglomeration of Ti3SiC2 nanosheets on the surface of the whiskers, promote the uniform spreading of nanosheets on the surface of the whiskers, and form a filler with good dispersion. Uniformly dispersed Ti3SiC2 nanosheets can maximize their reinforcing effect. When subjected to external forces, they can form a synergistic reinforcement effect with SiC whiskers, effectively transfer stress, and prevent material damage caused by stress concentration. Secondly, iron doping has a significant effect on improving the mechanical properties of Ti3SiC2 nanosheets. The doped iron atoms can partially replace the titanium atoms in the Ti3SiC2 lattice, introduce lattice distortion and strain field, and increase the dislocation density and grain boundary strength of the material. This change in microstructure can significantly enhance the bending strength and hardness of Ti3SiC2 nanosheets, enabling them to more effectively bear external forces and hinder the expansion of cracks. It should be emphasized that the precise control of the iron doping concentration plays a key role in achieving performance improvement. By strictly limiting the iron doping concentration to the range of 1.2-3.5at%, the best balance can be achieved in promoting uniform dispersion of Ti3SiC2 nanosheets and improving mechanical properties. Too low doping concentration is difficult to cause significant performance improvement, while too high doping concentration may lead to the destruction of the Ti3SiC2 nanosheet lattice structure and the decline of mechanical properties. Therefore, the iron doping concentration of 1.2-3.5 at% in this solution is the best range obtained through a large number of experimental optimizations, which can maximize the enhancement effect of iron doping while ensuring the structural integrity of Ti3SiC2 nanosheets. In summary, the technical solution of the present invention not only promotes the uniform dispersion of Ti3SiC2 nanosheets on the surface of SiC whiskers by introducing 1.2-3.5 at% iron doping into Ti3SiC2 nanosheets, but also significantly improves the mechanical properties of the material such as bending strength, fracture toughness and wear resistance through multiple mechanisms.This composite strategy of highly dispersible, high-strength and high-toughness iron-doped Ti3SiC2 nanosheets and SiC whiskers provides new ideas and solutions for the development of high-performance inorganic nano-modified floor base materials for artistic paints, and is expected to promote the upgrading and application expansion of artistic floor materials.

[0027] An important design purpose of the technical solution of the present invention is to develop a high-performance styrene-ethylene-butylene-styrene (SEBS) block copolymer chopped fiber as a toughening phase and crack resistance phase of the composite material, so as to further improve the fracture toughness and impact resistance of the inorganic nano-modified floor base material for artistic paint. In order to achieve this goal, this solution adopts an electrospinning process to prepare SEBS block copolymer fibers, and introduces hydroxyl-modified boron nitride nanotubes as nanofillers. Through the synergistic effect of the two, the mechanical properties and interfacial bonding properties of SEBS fibers are significantly enhanced. First, this solution adopts an electrospinning process to prepare SEBS block copolymer fibers. This method has the advantages of simple operation, controllable fiber diameter, and good orientation. By optimizing the mixing ratio of SEBS and tetrahydrofuran, the process parameters of electrospinning, such as applied voltage, solution injection speed, and working distance, SEBS long fibers with uniform diameter can be obtained. Subsequently, the long fibers are dried and chopped to prepare the required SEBS chopped fibers. This type of chopped fiber has the characteristics of moderate aspect ratio, large specific surface area, and easy dispersion. It can form a three-dimensional network structure in the composite matrix. Through mechanisms such as fiber bridging and crack deflection, it can effectively absorb and dissipate the stress caused by external forces, thereby improving the fracture toughness and impact resistance of the material. Secondly, this scheme introduces hydroxyl-modified boron nitride nanotubes as nanofillers when preparing SEBS chopped fibers, further enhancing the mechanical properties and interfacial bonding properties of the fibers. Boron nitride nanotubes have excellent mechanical strength, toughness and thermal conductivity, but their chemical inertness and hydrophobicity limit their dispersibility and interfacial bonding in the polymer matrix. In order to solve this problem, this scheme uses a strong acid mixed solution to modify the surface of boron nitride nanotubes by hydroxylation, introduces hydrophilic hydroxyl functional groups, and significantly improves its surface activity and compatibility with the polymer matrix. The hydroxyl-modified boron nitride nanotubes can be evenly dispersed in the SEBS matrix, and form strong interactions such as hydrogen bonds with the SEBS molecular chains, thereby enhancing the interfacial bonding between the nanotubes and the matrix. At the same time, the high strength and high modulus characteristics of nanotubes can effectively enhance the mechanical properties of SEBS fibers and improve their tensile strength and modulus. In addition, hydroxyl-modified boron nitride nanotubes can also enhance the interfacial bonding performance between SEBS chopped fibers and the composite matrix through multiple mechanisms. On the one hand, the hydroxyl functional groups on the surface of the nanotubes can form chemical bonds or physical entanglements with the polar groups in the composite matrix, thereby enhancing the interfacial bonding force between the fibers and the matrix. On the other hand, the uniformly dispersed nanotubes can form a nanoscale rough structure on the fiber surface, thereby increasing the friction and mechanical bite force between the fibers and the matrix. In summary, the technical solution of the present invention prepares SEBS block copolymer chopped fibers through an electrospinning process, and introduces hydroxyl-modified boron nitride nanotubes as nanofillers, thereby significantly enhancing the mechanical properties and interfacial bonding properties of SEBS fibers.This high-toughness, high-bonding SEBS chopped fiber can play a role in toughening and crack resistance in inorganic nano-modified floor base materials for artistic paint. Through mechanisms such as fiber bridging and crack deflection, it can effectively absorb and dissipate stress caused by external forces, and improve the fracture toughness and impact resistance of the material. At the same time, the multiple synergistic reinforcement effects between nanotubes, fibers, and matrix further improve the mechanical properties and service stability of the material, providing a new solution for the development of high-performance, long-life artistic floor materials.

[0028] The various raw material components in the technical solution of the present invention play different but complementary roles, and together construct an inorganic nano-modified ground base material for artistic paint with excellent performance. Among them, aluminate cement and silicate cement, as the main cementitious materials, form a dense skeleton structure with aggregates such as quartz sand and light calcium carbonate, and continuously enhance the strength of the material through hydration reaction; calcium sulfoaluminate can adjust the setting time and hydration process of cement; polycarboxylic acid water-reducing agent powder can effectively reduce the water consumption of material hydration and improve working performance; acrylic resin can improve the bonding strength and durability of the material; cellulose ether suspending agents, such as hydroxypropyl methylcellulose, can increase the viscosity of the material, prevent aggregate sedimentation, and ensure the uniformity of the material; silica sol can fill the pores and improve the density and strength of the material; defoaming agents such as BYK-028 or BYK-034 can eliminate bubbles generated during the mixing process of the material to avoid the decrease in strength caused by bubbles; dispersants such as sodium polyacrylate can improve the dispersibility of the various components of the material and prevent agglomeration; preservatives such as 2-octyl-4-isothiazoline-3-one can inhibit the growth of microorganisms and extend the shelf life of the material.

[0029] The present invention also provides a method for preparing an inorganic nano-modified ground base material for artistic paint, comprising the following steps:

[0030] S1. Prepare component A: add surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylic acid water-reducing agent powder, cellulose ether suspension agent and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 30 to 50 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue to stir in forward and reverse directions for 45 to 60 minutes.

[0031] S2. Prepare component B: Start the low-speed disperser, put water, silica sol, defoamer, dispersant and preservative into the dispersion tank in sequence, and disperse at a low speed for 10 to 15 minutes.

[0032] S3. Prepare the ground base material: mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 60-80rpm for 10-20min, then stir at a high speed of 120-150rpm for 35-50min, until mixed evenly. Let it stand for 8-12min after stirring. After the mixture foams slightly, stir it again at a low speed of 60-80rpm for 30-60s to eliminate the bubbles generated by stirring. Pour the mixed slurry onto the base surface, apply it evenly with a long-tooth scraper, control the coating thickness to be uniform, then use a barbed roller to roll and degas, and carefully trim the surface. Wait until the slurry is completely solidified.

[0033] (3) Beneficial technical effects

[0034] 1. The present invention innovatively develops inorganic nano-modified ground base materials for artistic paint. By introducing surface-modified doped Ti3SiC2 / SiC fillers, and utilizing micro-nano multi-scale structural design and surface modification technology, the compressive strength, hardness and flexibility of the material are significantly enhanced, solving the problem that traditional materials have difficulty in taking into account strength, hardness and flexibility. The material is modified by 3-aminopropylmethyldimethoxysilane, which improves the interfacial bonding and physical compatibility between the filler and the matrix, reduces cracking, sanding and other phenomena, and enhances the overall beauty and durability of the artistic coating. At the same time, its excellent mechanical properties reduce the amount of materials and layer thickness, reduce costs, improve construction efficiency, and extend the service life of the floor, reduce resource consumption and waste emissions, and have a positive effect on environmental protection and sustainable development.

[0035] 2. The present invention forms uniformly distributed fillers by in-situ growth of 1.2-3.5at% iron-doped Ti3SiC2 nanosheets on the surface of SiC whiskers, and utilizes the coherent interface between the iron-doped Ti3SiC2 nanosheets and the SiC whiskers to achieve a strengthened bond between the filler and the matrix, thereby significantly improving the comprehensive mechanical properties and wear resistance of the material. Compared with the prior art, this scheme has the following outstanding advantages: First, the design of in-situ growth and coherent interface ensures high-strength chemical bonding between the filler and the matrix, greatly improving the interface bonding strength and stability; Second, the doping of iron elements promotes the uniform dispersion of Ti3SiC2 nanosheets on the surface of SiC whiskers, and at the same time significantly enhances the bending strength and hardness of the filler through mechanisms such as lattice distortion and dislocation density enhancement; Third, the composite of nanosheets and whiskers plays a synergistic enhancement role, making up for the shortcomings of a single filler, so that the bending strength, fracture toughness and wear resistance of the material are comprehensively improved.

[0036] 3. The present invention aims to develop a high-performance styrene-ethylene-butylene-styrene (SEBS) block copolymer chopped fiber as a toughening phase and anti-cracking phase for inorganic nano-modified ground base materials for artistic paint. Compared with the prior art, this solution adopts an electrospinning process to prepare SEBS chopped fibers, and introduces hydroxyl-modified boron nitride nanotubes as nanofillers. Through the synergistic effect of the two, the fracture toughness, impact resistance and service stability of the material are significantly improved. Specifically, when the material is impacted by external force, the SEBS fiber network can effectively absorb and dissipate stress through mechanisms such as fiber bridging and crack deflection, thereby improving the fracture toughness and impact resistance of the material and delaying crack propagation. In addition, the introduction of hydroxyl-modified boron nitride nanotubes further enhances the mechanical properties and interfacial bonding properties of SEBS fibers.

[0037] 4. In the technical solution of the present invention, various raw materials work together to construct a high-performance artistic paint base material. Aluminate and silicate cement combine with aggregate to form a solid skeleton, calcium sulfoaluminate adjusts the setting time, water reducer improves workability, and acrylic resin enhances adhesion and durability. Cellulose ether increases viscosity and prevents sedimentation, silica sol improves density, defoamer removes bubbles and maintains strength, dispersant prevents agglomeration, and preservatives prevent microorganisms, which together ensure that the material performance is excellent and stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the original SEM scanning electron microscope morphology image of the SiC whisker used in Example 1 of the present invention.

[0039] Figure 2 This is a SEM scanning electron microscope morphology image of the Ti3SiC2 / SiC filler prepared in Example 1 of the present invention.

[0040] Figure 3 This is the XRD phase analysis diagram of the original SiC whisker and the prepared Ti3SiC2 / SiC filler in Example 1 of the present invention.

[0041] Figure 4 This is a TEM transmission electron microscope image of the Ti3SiC2 / SiC filler interface prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0043] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0044] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0045]

[0046]

[0047] Example 1

[0048] An inorganic nano-modified ground base material for artistic paint consists of component A and component B in a mass ratio of 4:1.

[0049] Component A is composed of the following raw materials in parts by mass: 5 parts of surface modified doped Ti3SiC2 / SiC filler, 2 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 5 parts of aluminate cement, 30 parts of 52.5 grade silicate cement, 15 parts of quartz sand, 5 parts of light calcium carbonate, 0.2 parts of calcium sulfoaluminate, 0.1 parts of polycarboxylate water reducer powder, 0.1 parts of acrylic resin, and 0.1 parts of hydroxypropyl methylcellulose.

[0050] Component B is composed of the following raw materials in parts by mass: 50 parts of water, 3 parts of silica sol, 0.1 parts of BYK-028, 0.5 parts of sodium polyacrylate, and 0.1 parts of 2-n-octyl-4-isothiazoline-3-one.

[0051] The surface-modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler comprises SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers; the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whiskers in an in-situ growth manner; the interface between the doped Ti3SiC2 nanosheets and the SiC whiskers is a coherent interface; the doping element of the doped Ti3SiC2 nanosheets is iron, and the doping concentration is 1.2at%; the diameter of the SiC whiskers is 2μm, and the length is 20μm.

[0052] The preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: after mixing 10 parts of polycarbosilane, 5 parts of Ti powder, 0.5 parts of ferrocene and 60 parts of tetrahydrofuran by weight, 8 parts of SiC whisker are added and stirred for 2 hours, and then dried completely in a vacuum drying oven at room temperature, and then placed in a vacuum tube furnace, and heat treated at 1300°C for 2 hours under an argon atmosphere, and then cooled to obtain the doped Ti3SiC2 / SiC filler. After mixing 3 parts of 3-aminopropylmethyldimethoxysilane and 50 parts of anhydrous ethanol, 20 parts of the doped Ti3SiC2 / SiC filler are added, stirred at 60°C for 2 hours, and after stirring, the solution is removed by suction filtration, and then the filtered residue is vacuum dried at room temperature for 4 hours to obtain the surface modified doped Ti3SiC2 / SiC filler.

[0053] The preparation method of styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 4 parts of boron nitride nanotubes are ultrasonically treated in 100 parts of a 10 g / L H2SO4 / HNO3 mixed acid solution with a mass ratio of 1:1 for 10 hours, then stirred at 60°C for 8 hours, and then the ultrasonic mixture is centrifuged at 5000 r / min for 10 minutes, and then the centrifuged precipitate is washed with deionized water until neutral, and finally dried in vacuum at room temperature. Then, 20 parts of styrene-ethylene-butylene-styrene block copolymer, 3 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran were magnetically stirred and mixed for 12 hours, and then the solution was loaded into an electrospinning syringe. Then, the electrospinning process was used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers were dried and chopped into styrene-ethylene-butylene-styrene block copolymer short fibers. The process parameters of electrospinning were: temperature of 20°C, humidity of about 35%, applied voltage of 10 kV, solution injection speed of 3 mL / h, and working distance between the needle tip and the collector of 15 cm.

[0054] The method for preparing an inorganic nano-modified ground base material for artistic paint of this embodiment comprises the following steps:

[0055] S1. Prepare component A: add surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylic acid water-reducing agent powder, hydroxypropyl methylcellulose and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 30 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue stirring in forward and reverse directions for 45 minutes.

[0056] S2. Prepare component B: Start the low-speed disperser, put water, silica sol, defoamer, dispersant and preservative into the dispersion tank in sequence, and disperse at a low speed for 10 minutes.

[0057] S3. Prepare the ground base material: mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 60 rpm for 10 minutes, then stir at a high speed of 120 rpm for 35 minutes, until the mixture is evenly mixed. After stirring, let it stand for 8 minutes. After the mixture foams slightly, stir it again at a low speed of 60 rpm for 30 seconds to eliminate the bubbles generated by stirring. Pour the mixed slurry onto the base surface, apply it evenly with a long-toothed scraper, control the coating thickness to be uniform, then use a barbed roller to roll and degas, and carefully trim the surface. Wait until the slurry is completely solidified.

[0058] Through a series of characterization analysis of Example 1, the following conclusions can be drawn: The SEM scanning electron microscope morphology shows that the original SiC whiskers present a typical linear structural feature ( Figure 1 ), while after surface modification and Ti3SiC2 doping, the surface of SiC whiskers is evenly dispersed with Ti3SiC2 nanosheets ( Figure 2 ), proving that Ti3SiC2 and SiC have achieved effective composite. XRD phase analysis further confirmed that the modified Ti3SiC2 / SiC filler retains the characteristic peak of SiC while showing the characteristic diffraction peak of Ti3SiC2 ( Figure 3 ), indicating that there are two phases of SiC and Ti3SiC2 in the composite filler. In addition, the TEM image of the Ti3SiC2 / SiC filler interface ( Figure 4 ) clearly shows that the interface between Ti3SiC2 and SiC is continuous and has no obvious defects, proving that a good coherent interface is formed between the two substances. In summary, through systematic electron microscopy characterization and phase analysis, it is fully proved that Example 1 successfully prepared Ti3SiC2 / SiC composite filler with Ti3SiC2 nanosheets uniformly dispersed on the surface of SiC whiskers, and an ideal coherent interface structure was constructed between Ti3SiC2 and SiC, which laid a foundation for improving the performance of the composite material.

[0059] Example 2

[0060] An inorganic nano-modified ground base material for artistic paint consists of component A and component B in a mass ratio of 4:1.

[0061] Component A is composed of the following raw materials in parts by mass: 7 parts of surface modified doped Ti3SiC2 / SiC filler, 3 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 7 parts of aluminate cement, 33 parts of 52.5 grade silicate cement, 18 parts of quartz sand, 7 parts of light calcium carbonate, 0.4 parts of calcium sulfoaluminate, 0.2 parts of polycarboxylate water reducer powder, 0.4 parts of acrylic resin, and 0.2 parts of sodium carboxymethyl cellulose.

[0062] Component B is composed of the following raw materials in parts by mass: 52 parts of water, 4 parts of silica sol, 0.2 parts of BYK-034, 0.6 parts of sodium polymethacrylate, and 0.1 parts of 1,2-benzisothiazol-3-one.

[0063] The surface-modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler comprises SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers; the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whiskers in an in-situ growth manner; the interface between the doped Ti3SiC2 nanosheets and the SiC whiskers is a coherent interface; the doping element of the doped Ti3SiC2 nanosheets is iron, and the doping concentration is 2.1at%; the diameter of the SiC whiskers is 3μm, and the length is 29μm.

[0064] The preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: after mixing 13 parts of polycarbosilane, 7 parts of Ti powder, 0.7 parts of ferrocene and 75 parts of tetrahydrofuran by weight, 10 parts of SiC whiskers are added and stirred for 3 hours, and then dried completely in a vacuum drying oven at room temperature, and then placed in a vacuum tube furnace, and heat treated at a temperature of 1380°C for 3 hours under an argon atmosphere, and then cooled to obtain the doped Ti3SiC2 / SiC filler. After mixing 4 parts of 3-aminopropylmethyldimethoxysilane and 60 parts of anhydrous ethanol, 29 parts of the doped Ti3SiC2 / SiC filler are added, stirred at 66°C for 3 hours, and after stirring, the solution is removed by suction filtration, and then the filtered residue is vacuum dried at room temperature for 6 hours to obtain the surface modified doped Ti3SiC2 / SiC filler.

[0065] The preparation method of styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 6 parts of boron nitride nanotubes are ultrasonically treated in 100 parts of a 10 g / L H2SO4 / HNO3 mixed acid solution with a mass ratio of 1:1 for 12 hours, then stirred at 63°C for 8 hours, and then the ultrasonic mixture is centrifuged at 5300 r / min for 13 minutes, and then the centrifuged precipitate is washed with deionized water until neutral, and finally dried in vacuum at room temperature. Then, 29 parts of styrene-ethylene-butylene-styrene block copolymer, 5 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran were magnetically stirred and mixed for 15 hours, and then the solution was loaded into an electrospinning syringe. Then, the electrospinning process was used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers were dried and chopped into styrene-ethylene-butylene-styrene block copolymer short fibers. The process parameters of electrospinning were: temperature of 22°C, humidity of about 38%, applied voltage of 11 kV, solution injection speed of 3 mL / h, and working distance between needle tip and collector of 17 cm.

[0066] The method for preparing an inorganic nano-modified ground base material for artistic paint of this embodiment comprises the following steps:

[0067] S1. Prepare component A: add surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylic acid water-reducing agent powder, sodium carboxymethyl cellulose and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 38 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue stirring in forward and reverse directions for 50 minutes.

[0068] S2. Prepare component B: Start the low-speed disperser, put water, silica sol, BYK-034, sodium polymethacrylate and 1,2-benzisothiazol-3-one into the dispersion tank in sequence, and disperse at a low speed for 12 minutes.

[0069] S3. Prepare ground base material: mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 66 rpm for 13 minutes, then stir at a high speed of 132 rpm for 41 minutes, until mixed evenly. Let it stand for 10 minutes after stirring. After the mixture foams slightly, stir it again at a low speed of 66 rpm for 43 seconds to eliminate the bubbles generated by stirring. Pour the mixed slurry onto the base surface, apply it evenly with a long-toothed scraper, control the coating thickness to be uniform, then use a barbed roller to roll and degas, and carefully trim the surface. Wait until the slurry is completely solidified.

[0070] Example 3

[0071] An inorganic nano-modified ground base material for artistic paint consists of a component A and a component B in a mass ratio of 4:1.

[0072] Component A is composed of the following raw materials in parts by mass: 9 parts of surface modified doped Ti3SiC2 / SiC filler, 4 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 8 parts of aluminate cement, 36 parts of 52.5 grade silicate cement, 21 parts of quartz sand, 8 parts of light calcium carbonate, 0.6 parts of calcium sulfoaluminate, 0.3 parts of polycarboxylate water reducer powder, 0.7 parts of acrylic resin, and 0.3 parts of hydroxyethyl cellulose.

[0073] Component B is composed of the following raw materials in parts by mass: 53 parts of water, 4 parts of silica sol, 0.2 parts of BYK-028, 0.7 parts of sodium polyacrylate, and 0.2 parts of 2-methyl-4-isothiazoline-3-one.

[0074] The surface modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler comprises SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers; the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whiskers in an in-situ growth manner; the interface between the doped Ti3SiC2 nanosheets and the SiC whiskers is a coherent interface; the doping element of the doped Ti3SiC2 nanosheets is iron, and the doping concentration is 2.6at%; the diameter of the SiC whiskers is 3μm, and the length is 35μm.

[0075] The preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: after mixing 15 parts of polycarbosilane, 8 parts of Ti powder, 0.8 parts of ferrocene and 84 parts of tetrahydrofuran by weight, 12 parts of SiC whiskers are added and stirred for 3 hours, and then dried completely in a vacuum drying oven at room temperature, and then placed in a vacuum tube furnace, heat treated at a temperature of 1400°C for 3 hours under an argon atmosphere, and then cooled to obtain the doped Ti3SiC2 / SiC filler. After mixing 5 parts of 3-aminopropylmethyldimethoxysilane and 68 parts of anhydrous ethanol, 35 parts of the doped Ti3SiC2 / SiC filler are added, stirred at 72°C for 3 hours, and after stirring, the solution is removed by suction filtration, and then the filtered residue is vacuum dried at room temperature for 6 hours to obtain the surface modified doped Ti3SiC2 / SiC filler.

[0076] The preparation method of styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 7 parts of boron nitride nanotubes are ultrasonically treated in 100 parts of a H2SO4 / HNO3 mixed acid solution with a mass ratio of 1:1 and a concentration of 10 g / L for 13 hours, and then stirred at 66°C for 8 hours. The ultrasonic mixture is then centrifuged at 5500 r / min for 15 minutes, and the centrifuged precipitate is then washed with deionized water until it is neutral, and finally dried in vacuum at room temperature. Then, 35 parts of styrene-ethylene-butylene-styrene block copolymer, 6 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran were magnetically stirred for 17 hours, and then the solution was loaded into an electrospinning syringe. Then, the electrospinning process was used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers were dried and chopped into styrene-ethylene-butylene-styrene block copolymer short fibers. The process parameters of electrospinning were: temperature of 23°C, humidity of about 41%, applied voltage of 11 kV, solution injection speed of 4 mL / h, and working distance between needle tip and collector of 18 cm.

[0077] The method for preparing an inorganic nano-modified ground base material for artistic paint in this embodiment comprises the following steps:

[0078] S1. Prepare component A: add surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylic acid water-reducing agent powder, hydroxyethyl cellulose and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 42 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue to stir in forward and reverse directions for 54 minutes.

[0079] S2. Prepare component B: Start the low-speed disperser, put water, silica sol, BYK-028, sodium polyacrylate and 2-methyl-4-isothiazoline-3-one into the dispersion tank in sequence, and disperse at a low speed for 13 minutes.

[0080] S3. Prepare the ground base material: mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 72rpm for 16min, then stir at a high speed of 138rpm for 44min, until mixed evenly, let it stand for 10min after stirring, stir again at a low speed of 72rpm for 48s after the mixture foams slightly, eliminate the bubbles generated by stirring, pour the mixed slurry onto the base surface, apply it evenly with a long-tooth scraper, control the coating thickness to be uniform, then use a barbed roller to roll and degas, and carefully trim the surface until the slurry is completely solidified.

[0081] Example 4

[0082] An inorganic nano-modified ground base material for artistic paint consists of a component A and a component B in a mass ratio of 4:1.

[0083] Component A is composed of the following raw materials in parts by mass: 12 parts of surface modified doped Ti3SiC2 / SiC filler, 6 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 10 parts of aluminate cement, 40 parts of 52.5 grade silicate cement, 25 parts of quartz sand, 10 parts of light calcium carbonate, 0.8 parts of calcium sulfoaluminate, 0.5 parts of polycarboxylate water reducer powder, 1 part of acrylic resin, and 0.5 parts of hydroxypropyl methylcellulose.

[0084] Component B is composed of the following raw materials in parts by mass: 55 parts of water, 5 parts of silica sol, 0.3 parts of BYK-034, 0.8 parts of sodium polymethacrylate, and 0.2 parts of 2-n-octyl-4-isothiazoline-3-one.

[0085] The surface modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler comprises SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers; the doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whiskers in an in-situ growth manner; the interface between the doped Ti3SiC2 nanosheets and the SiC whiskers is a coherent interface; the doping element of the doped Ti3SiC2 nanosheets is iron, and the doping concentration is 3.5at%; the diameter of the SiC whiskers is 4μm, and the length is 45μm.

[0086] The preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: after mixing 18 parts of polycarbosilane, 10 parts of Ti powder, 1 part of ferrocene and 100 parts of tetrahydrofuran by weight, 15 parts of SiC whiskers are added and stirred for 4 hours, and then dried completely in a vacuum drying oven at room temperature, and then placed in a vacuum tube furnace, heat treated at a temperature of 1500°C for 4 hours under an argon atmosphere, and then cooled to obtain the doped Ti3SiC2 / SiC filler. After mixing 6 parts of 3-aminopropylmethyldimethoxysilane and 80 parts of anhydrous ethanol, 45 parts of the doped Ti3SiC2 / SiC filler are added, stirred at 80°C for 4 hours, and after stirring, the solution is removed by suction filtration, and then the filtered residue is vacuum dried at room temperature for 8 hours to obtain the surface modified doped Ti3SiC2 / SiC filler.

[0087] The preparation method of styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 9 parts of boron nitride nanotubes are ultrasonically treated in 100 parts of a H2SO4 / HNO3 mixed acid solution with a concentration of 10 g / L and a mass ratio of 1:1 for 15 hours, and then stirred at 70°C for 8 hours, and then the ultrasonic mixture is centrifuged at a speed of 6000 r / min for 18 minutes, and then the precipitate after centrifugation is washed with deionized water until it is neutral, and finally vacuum dried at room temperature. Then, 45 parts of styrene-ethylene-butylene-styrene block copolymer, 8 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran were magnetically stirred for 20 hours, and then the solution was loaded into an electrospinning syringe. Then, the electrospinning process was used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers were dried and chopped into styrene-ethylene-butylene-styrene block copolymer short fibers. The process parameters of electrospinning were: temperature of 25°C, humidity of about 45%, applied voltage of 12 kV, solution injection speed of 4 mL / h, and a working distance of 20 cm between the needle tip and the collector.

[0088] The method for preparing an inorganic nano-modified ground base material for artistic paint in this embodiment comprises the following steps:

[0089] S1. Prepare component A: add surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylic acid water-reducing agent powder, hydroxypropyl methylcellulose and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 50 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue to stir in forward and reverse directions for 60 minutes.

[0090] S2. Prepare component B: Start the low-speed disperser, put water, silica sol, BYK-034, sodium polymethacrylate, and 2-n-octyl-4-isothiazoline-3-one into the dispersion tank in sequence, and disperse at a low speed for 15 minutes.

[0091] S3. Prepare the ground base material: mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 80rpm for 20min, then stir at a high speed of 150rpm for 50min, until mixed evenly, let it stand for 12min after stirring, stir again at a low speed of 80rpm for 60s after the mixture foams slightly, eliminate the bubbles generated by stirring, pour the mixed slurry onto the base surface, apply it evenly with a long-tooth scraper, control the coating thickness to be uniform, then use a barbed roller to roll and degas, and carefully trim the surface until the slurry is completely solidified.

[0092] Example 5

[0093] It is basically the same as Example 1, except that the amount of surface-modified doped Ti3SiC2 / SiC filler added in the preparation of the ground base material is 12 parts.

[0094] Comparative Example 1

[0095] It is basically the same as Example 1, except that the surface-modified doped Ti3SiC2 / SiC filler is replaced by an equal amount of surface-modified SiC whisker filler.

[0096] The preparation method of surface modified SiC whisker filler is as follows: after evenly mixing 3 parts of 3-aminopropylmethyldimethoxysilane and 50 parts of anhydrous ethanol, 20 parts of SiC whisker filler are added, and the mixture is stirred at 60°C for 2 hours. After the stirring, the solution is removed by filtration, and then the filtered residue is vacuum dried at room temperature for 4 hours to obtain surface modified doped SiC whisker filler.

[0097] Comparative Example 2

[0098] It is basically the same as Example 1, except that the surface-modified doped Ti3SiC2 / SiC filler is not subjected to surface modification treatment.

[0099] Comparative Example 3

[0100] It is basically the same as Example 1, except that ferrocene is not added in the preparation of the surface-modified doped Ti3SiC2 / SiC filler, that is, the surface-modified doped Ti3SiC2 / SiC filler is not doped.

[0101] Comparative Example 4

[0102] The method is basically the same as Example 1, except that hydroxyl-modified boron nitride nanotubes are not added in the preparation of styrene-ethylene-butylene-styrene block copolymer chopped fibers.

[0103] Performance Test:

[0104] Wear resistance: When evaluating the durability of ground sub-materials, wear resistance is a critical consideration. To achieve this evaluation, refer to GB / T 16925-1997 Test method for wear resistance of concrete and its products (ball bearing method), weigh the mass of the sample before and after wear, and calculate the wear resistance.

[0105] Hardness: Tested in accordance with GB / T 17671-1999 "Test Method for Cement Mortar Strength". Sample: Prepare the ground sub-material into a 40mm×40mm×160mm test piece, measure the Rockwell hardness value of the sample surface, measure 5 points for each sample, and take the average value as the sample hardness value.

[0106] Temperature stability test: Inorganic nano-modified materials are used to replace part of the cement to prepare 40mm×40mm×160mm cement mortar prism specimens. Test conditions: The specimen is placed in a high and low temperature alternating test chamber, and 5 cycles are performed under the conditions of -18℃, 16h; room temperature, 4h; 50℃, 4h, to observe whether the specimen has cracking. After 5 temperature cycles, it is judged that the specimen should have no cracking, falling off, etc. If there is no cracking, falling off, etc., it is qualified, otherwise it is unqualified.

[0107] Flexibility test: According to the conventional microcement process and patented material process, a microcement sample with a thickness of 3mm±0.1mm is made on 200mm×200mm×0.5mm PP paper. Test process: Fix the sample at one end, slowly bend the PP paper to 90 degrees, and observe whether the microcement sample cracks or breaks. If the sample cracks or breaks, it is considered that the flexibility is unqualified.

[0108] The ground base materials of the coatings of Examples 1 to 5 and Comparative Examples 1 to 4 are summarized in Table 2.

[0109] Table 2 Performance of the ground sub-materials of Examples 1 to 7 and Comparative Examples 1 to 4

[0110]

[0111]

[0112] The main difference between Comparative Example 1 and Example 1 is that the surface modified doped Ti3SiC2 / SiC filler is replaced by an equal amount of surface modified SiC whisker filler. From Table 2, it can be seen that the presence of Ti3SiC2 can significantly improve the hardness, wear resistance, temperature stability and flexibility of the material, because Ti3SiC2 and SiC have a better synergistic reinforcement effect, and the layered structure of Ti3SiC2 can also improve the flexibility of the material.

[0113] The main difference between Comparative Example 2 and Example 1 is whether the doped Ti3SiC2 / SiC filler is surface modified. It can be seen from Table 2 that the Rockwell hardness, wear resistance, temperature stability and flexibility of Example 1 are better than those of Comparative Example 2. This is because surface modification can significantly improve the interface bonding between the filler and the matrix, and improve the mechanical properties and service life of the composite material.

[0114] In comparative example 3, ferrocene was not added for doping treatment when preparing the surface modified doped Ti3SiC2 / SiC filler, resulting in unsatisfactory dispersibility and bonding strength of the filler. As can be seen from Table 2, the Rockwell hardness, wear resistance, temperature stability and flexibility of Example 1 are better than those of comparative example 3, because ferrocene can improve the dispersibility of the filler in the matrix, reduce agglomeration, and improve the bonding strength between the filler and the matrix, thereby comprehensively improving the performance of the composite material.

[0115] In Comparative Example 4, hydroxyl-modified boron nitride nanotubes were not added when preparing styrene-ethylene-butylene-styrene block copolymer chopped fibers, resulting in the composite material having poor Rockwell hardness, wear resistance, temperature stability and flexibility. This is because the boron nitride nanotubes mainly play the role of toughening and improving the mechanical properties of the polymer matrix.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. An inorganic nano-modified ground base material for artistic paint, characterized in that: It is composed of component A and component B in a mass ratio of 4:1; The component A is composed of the following raw materials in parts by mass: 5 to 12 parts of surface modified doped Ti3SiC2 / SiC filler, 2 to 6 parts of styrene-ethylene-butylene-styrene block copolymer chopped fibers, 5 to 10 parts of aluminate cement, 30 to 40 parts of 52.5 grade silicate cement, 15 to 25 parts of quartz sand, 5 to 10 parts of light calcium carbonate, 0.2 to 0.8 parts of calcium sulfoaluminate, 0.1 to 0.5 parts of polycarboxylate water reducer powder, 0.1 to 1 parts of acrylic resin, and 0.1 to 0.5 parts of cellulose ether suspending agent; The component B is composed of the following raw materials in parts by mass: 50-55 parts of water, 3-5 parts of silica sol, 0.1-0.3 parts of defoaming agent, 0.5-0.8 parts of dispersant, and 0.1-0.2 parts of preservative; The surface-modified doped Ti3SiC2 / SiC filler is obtained by surface-modifying the doped Ti3SiC2 / SiC filler with 3-aminopropylmethyldimethoxysilane; the doped Ti3SiC2 / SiC filler comprises SiC whiskers and doped Ti3SiC2 nanosheets loaded on the surface of the SiC whiskers; The doping element of the doped Ti3SiC2 nanosheet is iron, and the doping concentration is 1.2-3.5at%; The preparation method of the doped Ti3SiC2 / SiC filler is as follows: after mixing 10 to 18 parts of polycarbosilane, 5 to 10 parts of Ti powder, 0.5 to 1 part of ferrocene and 60 to 100 parts of tetrahydrofuran by weight, 8 to 15 parts of SiC whiskers are added, stirred for 2 to 4 hours, dried completely in a vacuum drying oven at room temperature, placed in a vacuum tube furnace, heat treated at a temperature of 1300 to 1500° C. for 2 to 4 hours in an argon atmosphere, and cooled to obtain the doped Ti3SiC2 / SiC filler; The method for preparing the styrene-ethylene-butylene-styrene block copolymer chopped fibers is as follows: by weight, 20 to 45 parts of styrene-ethylene-butylene-styrene block copolymer, 3 to 8 parts of hydroxyl-modified boron nitride nanotubes and 100 parts of tetrahydrofuran are magnetically stirred and mixed for 12 to 20 hours, and then the solution is loaded into an electrospinning syringe, and then an electrospinning process is used to obtain styrene-ethylene-butylene-styrene block copolymer long fibers, and then the long fibers are dried and chopped into styrene-ethylene-butylene-styrene block copolymer chopped fibers, wherein the process parameters of the electrospinning are: temperature of 20 to 25° C., humidity of 35 to 45%, applied voltage of 10 to 12 kV, solution injection speed of 3 to 4 mL / h, and a working distance of 15 to 20 cm between the needle tip and the collector.

2. The inorganic nano-modified ground base material for artistic paint according to claim 1, characterized in that: The doped Ti3SiC2 nanosheets are uniformly distributed on the surface of the SiC whisker in an in-situ growth manner; The interface between the doped Ti3SiC2 nanosheet and the SiC whisker is a coherent interface.

3. An inorganic nano-modified ground base material for artistic paint according to claim 1 or 2, characterized in that: The SiC whisker has a diameter of 2 to 4 μm and a length of 20 to 45 μm.

4. The inorganic nano-modified ground base material for artistic paint according to claim 1, characterized in that: The preparation method of the surface modified doped Ti3SiC2 / SiC filler is as follows: in parts by weight, 3 to 6 parts of 3-aminopropylmethyldimethoxysilane and 50 to 80 parts of anhydrous ethanol are evenly mixed, and then 20 to 45 parts of doped Ti3SiC2 / SiC filler are added, and stirred at 60 to 80°C for 2 to 4 hours. After the stirring is completed, the solution is removed by suction filtration, and then the filtered residue is vacuum dried at room temperature for 4 to 8 hours to obtain a surface modified doped Ti3SiC2 / SiC filler.

5. The inorganic nano-modified ground base material for artistic paint according to claim 1, characterized in that: The preparation method of the hydroxyl-modified boron nitride nanotubes is as follows: by weight, 4 to 9 parts of boron nitride nanotubes are ultrasonically treated in a H2SO4 / HNO3 mixed acid solution with a mass ratio of 1:1 and a concentration of 10 g / L for 10 to 15 hours, then stirred at 60 to 70°C for 8 hours, and then the ultrasonic mixture is centrifuged at a speed of 5000 to 6000 r / min for 10 to 18 minutes, and then the precipitate after centrifugation is washed with deionized water until it is neutral, and finally vacuum dried at room temperature.

6. The inorganic nano-modified ground base material for artistic paint according to claim 1, characterized in that: The cellulose ether suspending agent is hydroxypropyl methylcellulose or sodium carboxymethyl cellulose or hydroxyethyl cellulose; The defoamer is BYK-028 or BYK-034; The dispersant is sodium polyacrylate or sodium polymethacrylate; The preservative is 2-n-octyl-4-isothiazoline-3-one or 1,2-benzisothiazol-3-one or 2-methyl-4-isothiazoline-3-one.

7. The method for preparing an inorganic nano-modified ground base material for artistic paint according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Prepare component A: add the surface modified doped Ti3SiC2 / SiC filler, styrene-ethylene-butylene-styrene block copolymer chopped fibers, polycarboxylate water reducer powder, cellulose ether suspension and acrylic resin into the hopper, start the machine and stir in forward and reverse directions for 30 to 50 minutes, then add aluminate cement, 52.5 grade silicate cement, quartz sand, light calcium carbonate and calcium sulfoaluminate and continue to stir in forward and reverse directions for 45 to 60 minutes; S2. Preparation of component B: Start the low-speed disperser, put water, silica sol, defoamer, dispersant, and preservative into the dispersion tank in turn, and disperse at a low speed for 10 to 15 minutes; S3. Preparation of floor base material: Mix the prepared component A and component B in a mass ratio of 4:1, start the forced mixer, first stir at a low speed of 60-80rpm for 10-20min, then stir at a high speed of 120-150rpm for 35-50min, until mixed evenly. Let it stand for 8-12min after stirring. After the mixture is slightly foamed, stir it again at a low speed of 60-80rpm for 30-60s to eliminate the bubbles generated by stirring. Pour the mixed slurry onto the base surface, apply it evenly with a long-toothed scraper, control the coating thickness to be uniform, then use a thorny roller to roll and degas, and carefully trim the surface. After the slurry is completely solidified, the inorganic nano-modified floor base material for artistic paint is obtained.

Citation Information

Patent Citations

  • Metal-matrix composite with silicon carbide as reinforcing phase and preparation method of metal-matrix composite

    CN105925872A

  • Preparation method for in-situ generated Ti3SiC2-phase toughening silicon carbide ceramic matrix composite material

    CN108409347A